Unveiling the Association between Body Image Dissatisfaction and Dental Anxiety - Maayan Shacham; Lee Greenblatt-Kimron; Yaira Hamama-Raz; Eitan Mijiritsky; Menachem Ben-Ezra; Gerry Humphris (Surgeries, 2022)
Background: Increased demands for invasive and non-invasive treatments related to body image disturbances are seen worldwide. These demands may be related to body image dissatisfaction. No study to date investigated the relationship between body image dissatisfaction and dental anxiety (namely, anticipatory dental anxiety and treatment dental anxiety) among a non-clinical population. The current study aims to unveil such relationships. Methods: Dentally anxious people may choose to ‘cope’ with their anxiety via unnecessary invasive procedures related to their body image dissatisfaction. In the current study, 553 individuals completed an online survey assessing their dental anxiety, dental neglect, and body image via self-report questionnaires. Results: Body image dissatisfaction was significantly correlated with dental anxiety. In contrast to previous studies, dental neglect was negatively associated with dental anxiety. Additionally, no link was found between body image dissatisfaction and dental neglect. Conclusions: The current study highlights the importance of addressing these factors prior to invasive procedures.